PENGGUNAAN GAYA BAHASA DALAM NOVEL LAUT BERCERITA KARYA LEILA S. CHUDORI - Meitridwiastiti, Anak Agung Ayu (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2022)
This research on the use of language style in the novel Laut Bercerita (Sea Telling Stories) by Leila S. Chudori is a descriptive study. This study aims to describe the types of figurative language and the functions of the language styles contained in the novel Laut Bercerita. The data source of this research was the use of figurative language styles in the novel Laut Bercerita, in more detail on the aspects of the type of language style and the function of language style. The data were collected by reading the whole story carefully, thoroughly, and repeatedly and recording the language style and language function. The obtained data were then analyzed using descriptive analysis techniques. The data were classified into types of language style. The descriptive analysis of the types of figurative language was conducted to find the function of language style in the novel, and to conclude all discussions related to the language style in the novel Laut Bercerita. The results of this study showed that the types of language style in the novel are simile, litotes, metaphor, repetition, personification, synecdoche, hyperbole, and hypalase. The function of language style in the novel Laut Bercerita is to beautify the sound and narrative, explain the picture, emphasize the narrative or emotion, animate the picture, evoke a certain impression and atmosphere, and describe the feelings of the character. Keywords: language style, language function, Laut Bercerita, novel.